A determination of solar heat collection in sepertine copper and rubber pipe embedded in asphalt pavement using finite element method - Ahmad M.; Itam Z.B.; Beddu S.; Alanimi F.B.I.; Soanathan S.A.P. (Medwell Journals, 2023)
This project aimed to determine solar heat temperature variations in copper and rubber pipes embedded into the asphalt pavement using finite element method. The significant of the project to explore sustainable energy generation while using pavement surface as a heat collector therefore solar efficiency beneath paved surface has to determine. The arrangement of copper and rubber pipe in asphalt pavement is serpentine. The asphalt pavement size of 300300 and 300500 mm is simulated in ANSYS. Asphalt pavement is embedded with serpentine copper and rubber pipes of diameter of 40 mm. The solar heat temperature is collected in asphalt at depths of 50, 100 and 150 mm. Pipes are filled with liquid (water) to maintain or cool the temperature at night time. The stated asphalt pavement size samples have created where copper and rubber pipes are embedded and temperature collection among each sample is recorded. The findings of the project indicated that larger surface area of asphalt pavement (30500 mm) exposed to the Sunlight collect more energy than smaller (300300 mm) size of asphalt pavement. The serpentine arrangement of copper and rubber pipes embedded in asphalt pavement has slight difference of solar heat collections. The solar heat collected at 50 mm depth is higher than 100 and 150 mm depths. Medwell Journals, 2018.